Proteome‐wide analyses of human hepatocytes during differentiation and dedifferentiation. Issue 2 (1st July 2013) - Rowe, Cliff; Gerrard, Dave T.; Jenkins, Roz; Berry, Andrew; Durkin, Kesta; Sundstrom, Lars; Goldring, Chris E.; Park, B. Kevin; Kitteringham, Neil R.; Hanley, Karen Piper; Hanley, Neil A.
<x xml:space="preserve">Abstract</x> Failure to predict hepatotoxic drugs in preclinical testing makes it imperative to develop better liver models with a stable phenotype in culture. Stem cell‐derived models offer promise, with differentiated hepatocyte‐like cells currently considered to be "fetal‐like" in their maturity. However, this judgment is based on limited biomarkers or transcripts and lacks the required proteomic datasets that directly compare fetal and adult hepatocytes. Here, we quantitatively compare the proteomes of human fetal liver, adult hepatocytes, and the HepG2 cell line. In addition, we investigate the proteome changes in human fetal and adult hepatocytes when cultured in a new air‐liquid interface format compared to conventional submerged extracellular matrix sandwich culture. From albumin and urea secretion, and luciferase‐based cytochrome P450 activity, adult hepatocytes were viable in either culture model over 2 weeks. The function of fetal cells was better maintained in the air‐liquid interface system. Strikingly, the proteome was qualitatively similar across all samples but hierarchical clustering showed that each sample type had a distinct quantitative profile. HepG2 cells more closely resembled fetal than adult hepatocytes. Furthermore, clustering showed that primary adult hepatocytes cultured at the air‐liquid interface retained a proteome that more closely mimicked their fresh counterparts than conventional culture, which acquired myofibroblast features. Principal component analysis extended these findings and identified a simple set of proteins, including cytochrome P450 2A6, glutathione S transferase P, and alcohol dehydrogenases as specialized indicators of hepatocyte differentiation. Conclusion: Our quantitative datasets are the first that directly compare multiple human liver cells, define a model for enhanced maintenance of the hepatocyte proteome in culture, and provide a new protein "toolkit" for determining human hepatocyte maturity in cultured cells. (Hepatology 2013;58:799–809)